Village Sustainable Development Goals (Sdgs): Budgetary, Human Resources, And Technology Contributions - Nurul Listiawati; Muhammad Ihsan Ansari; Eni Novitasari; Dwi Noviana Fitri; Hisyam Ichsan; Taufik Hidayat B Tahawa (Politeknik Ganesha Medan, 2025)
This study aims to assess the impact of budget, human resources, and village technology on the achievement of Sustainable Development Goals (SDGs) in villages across West Sulawesi. By concentrating on West Sulawesi, the study offers insights into the specific challenges and opportunities of the local context, which could be applicable or adaptable to other regions in Indonesia. A quantitative and relational approach was employed to examine the contribution of key factors toward achieving the SDGs. The findings revealed that the budget has a negative and significant effect on the achievement of village sustainable development goals, human resources are crucial and play a vital role in reaching these goals, and technology is highly beneficial in advancing rural development objectives. The implementation phase of this research focuses on applying the insights gained from the study of how budgetary contributions, human resources, and technology can support the achievement of Sustainable Development Goals (SDGs) at the village level. This phase will involve practical steps for village governments, stakeholders, and community members to ensure successful outcomes. The implementation will be driven by participatory approaches, capacity-building programs, and the adoption of appropriate technologies, in line with budgetary allocations and available human resources. The expectation of this research is to increase transparency and accountability in budget allocation, clear strategies and support communities to use village budgets to address SDGs and increase local government and community involvement in resource allocation decisions.